Rheological investigations of water-soluble polysaccharides from the Tunisian brown seaweed Cystoseira compressa. (June 2020) - Hentati, Faiez; Pierre, Guillaume; Ursu, Alina Violeta; Vial, Christophe; Delattre, Cedric; Abdelkafi, Slim; Michaud, Philippe
Abstract: Rheological characteristics of a sodium alginate and a fucoidan extracted from the brown seaweed Cystoseira compressa harvested from Kerkennah island (Sfax, Tunisia) were investigated. Steady- shear flow and dynamical viscoelasticity were evaluated to describe physicochemical properties of the GulA- rich alginate (ManA/GulA, M/G = 0.77) and highly- ramified fucoidan in semi- diluted media depending on polymer concentration, shear rate, temperature, added mono- (KCl and NaCl) and divalent (CaCl2 ) salts. Alginate solutions exhibited shear- thinning behavior, with a temperature- dependent behavior highly correlated to the power- law model and the Arrhenius relationship. The results showed strong thixotropic and polyelectrolyte properties, influenced by addition of monovalent and divalent cations. The dynamic rheological characteristics showed a fluid- like viscoelastic behavior (tan δ  > 1) whereas the critical overlap concentration C* and specific polymer constant k s were respectively 11 g.L −1 and 4.4 using Williamson model. Fucoidan solutions displayed a shear - thinning behavior with a low viscoelasticity character influenced by temperature and monovalent salts. The flow and viscoelastic characteristics of polysaccharides were described by the Ostwald model. Graphical abstract: Investigation of flow behavior and dynamical viscoelasticity of water-soluble polysaccharides from C. compressa (Tunisian brown seaweed). Image 1 Highlights: An alginate and a fucoidan were extracted from the brown seaweed Cystoseira compressa. Rheological characteristics of the two polysaccharides were investigated. Alginate solutions exhibited shear- thinning and fluid- like viscoelastic behaviors. Fucoidan solutions displayed a shear - thinning behavior with a low viscoelasticity character.